2012
DOI: 10.2967/jnumed.111.090696
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of 18F-FDG PET Parameters and Plasma Epstein-Barr Virus DNA Load in Patients with Nasopharyngeal Carcinoma

Abstract: The plasma concentration of Epstein-Barr virus (EBV) DNA is associated with tumor burden and prognosis in patients with nasopharyngeal carcinoma (NPC), but data on the relationship between viral load and 18 F-FDG PET functional parameters are lacking. We examined the association of 18 F-FDG PET functional parameters and EBV DNA load with the clinicopathologic characteristics and clinical outcomes of patients with NPC. Methods: One hundred eight patients with NPC who underwent 18 F-FDG PET before treatment were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 44 publications
4
84
0
1
Order By: Relevance
“…All these studies showed that MTV/TLG were predictive for clinical outcome, with a higher predictive value than SUVmax. In (Chang et al, 2012), 108 patients with nasopharyngeal cancer treated with RT-CT were prospectively included to assess the predictive value of SUVMax, MTV and TLG for DFS and OS. Only Epstein-Barr virus DNA load and TLG of the tumor were significantly correlated with DFS and OS.…”
Section: Suvmax and Metabolic Tumor Volumementioning
confidence: 99%
“…All these studies showed that MTV/TLG were predictive for clinical outcome, with a higher predictive value than SUVmax. In (Chang et al, 2012), 108 patients with nasopharyngeal cancer treated with RT-CT were prospectively included to assess the predictive value of SUVMax, MTV and TLG for DFS and OS. Only Epstein-Barr virus DNA load and TLG of the tumor were significantly correlated with DFS and OS.…”
Section: Suvmax and Metabolic Tumor Volumementioning
confidence: 99%
“…The boundaries were drawn to include the primary tumor within the oropharynx on the axial 18 F-FDG PET/CT images. The lesions were automatically contoured at a threshold standardized uptake value (SUV) of 2.5 (7,23), and the voxels presenting an SUV intensity . 2.5 within the contouring margin were incorporated to define the MTV.…”
Section: Tlg Analysismentioning
confidence: 99%
“…The meta-analysis found that high pre-treatment levels of EBV DNA had good value as a prognostic indicator of survival and disease outcomes in patients with NPC. Most of the studies included in this meta-analysis found that increased levels of EBV DNA prior to treatment was associated with poor overall survival [13,[28][29][30][32][33][34][35][36][37]39,40]. Of the studies that evaluated the other outcomes, high pre-treatment EBV DNA levels was also associated with increased risk for disease progression, relapse, recurrence, and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 57 were fully evaluated for inclusion and 41 were eliminated for not reporting the outcomes of interest, reporting data that could not be pooled for a meta-analysis, not being relevant or reporting findings from a study that was already included. Sixteen studies were included in the study with a total of 7698 patients [12,13,[28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Three of the studies were retrospective in design and the remaining 13 studies were prospective (Table 1).…”
Section: Literature Searchmentioning
confidence: 99%